Traditional seed production - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1987)
Considerable progress can now be made, both in the field and in the drying and storage processes, to improve techniques for selecting and producing traditional seeds. In developing countries, 80% of the seeds used are produced by the farmers...